Inorganic Fertilizer Efficiency Using Liquid Organic Fertilizer on Peanut Growth and Production (Arachis hypogaea L.) - Dasumiati, Dasumiati; Nurrahmah, Annisa; Khairiah, Ardian; Junaidi, Junaidi; Altuhaish, Adeel Abdulkarim Fadhl (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2024)
Fertilization is important in increasing crop production. The use of liquid organic fertilizer (LOF) in addition to inorganic fertilizer in crop cultivation is expected to reduce the use of inorganic fertilizer and increase growth and production. The research aimed to determine the effect of LOF on peanut growth and production and to obtain the right dose to reduce the use of inorganic fertilizer doses. The research used a factorial Randomized Group Design (RGD) with two factors. The first factor was LOF dose (0, 3, 5, and 7 ml/L/Plot) and the second factor was inorganic fertilizer dose (0, 25, 50, and 100% of the recommended dose). Data analysis using ANOVA and DMRT. The results showed that the dose of LOF had a very significant effect (P0.01) on plant height, number of leaves, leaf area, number of filled pods, and total number of pods. The best dose in improving all these parameters was LOF 3 ml/L/Plot. The combination treatment of LOF and inorganic fertilizer had a very significant effect (P0.01) on the number of filled pods, but not significant effect (P0.05) on other parameters. The best combination of LOF dose and inorganic fertilizer was C1A1 (3 ml/L/Plot LOF + 25% Inorganic) which produced almost the same number of filled pods as C0A2 (0 ml/L/Plot LOF + 50% Inorganic), and higher than other treatments. The C1A3 treatment also produced higher fresh pod weight and dry pod weight than the other treatments. The application of LOF 3 ml/L/Plot + 25% inorganic fertilizer from the recommended dose can increase peanut production, and can reduce the use of inorganic fertilizer by 75%.